# Calculator search results

Formula
Solve the equation
Graph
$y = 0.3 x - 0.4$
$y = 0.2 x - 0.6$
$x$Intercept
$\left ( \dfrac { 4 } { 3 } , 0 \right )$
$y$Intercept
$\left ( 0 , - \dfrac { 2 } { 5 } \right )$
$x$Intercept
$\left ( 3 , 0 \right )$
$y$Intercept
$\left ( 0 , - \dfrac { 3 } { 5 } \right )$
$0.3x-0.4 = 0.2x-0.6$
$x = - 2$
 Solve a solution to $x$
$\color{#FF6800}{ 0.3 } \color{#FF6800}{ x } - 0.4 = 0.2 x - 0.6$
 Calculate the multiplication expression 
$\color{#FF6800}{ \dfrac { 3 x } { 10 } } - 0.4 = 0.2 x - 0.6$
$\dfrac { 3 x } { 10 } \color{#FF6800}{ - } \color{#FF6800}{ 0.4 } = 0.2 x - 0.6$
 Convert decimals to fractions 
$\dfrac { 3 x } { 10 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 5 } } = 0.2 x - 0.6$
$\dfrac { 3 x } { 10 } - \dfrac { 2 } { 5 } = \color{#FF6800}{ 0.2 } \color{#FF6800}{ x } - 0.6$
 Calculate the multiplication expression 
$\dfrac { 3 x } { 10 } - \dfrac { 2 } { 5 } = \color{#FF6800}{ \dfrac { x } { 5 } } - 0.6$
$\dfrac { 3 x } { 10 } - \dfrac { 2 } { 5 } = \dfrac { x } { 5 } \color{#FF6800}{ - } \color{#FF6800}{ 0.6 }$
 Convert decimals to fractions 
$\dfrac { 3 x } { 10 } - \dfrac { 2 } { 5 } = \dfrac { x } { 5 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 5 } }$
$\color{#FF6800}{ \dfrac { 3 x } { 10 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 5 } } = \color{#FF6800}{ \dfrac { x } { 5 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 5 } }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } = \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$3 x - 4 = \color{#FF6800}{ 2 } \color{#FF6800}{ x } - 6$
 Move the variable to the left-hand side and change the symbol 
$3 x - 4 \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = - 6$
$3 x \color{#FF6800}{ - } \color{#FF6800}{ 4 } - 2 x = - 6$
 Move the constant to the right side and change the sign 
$3 x - 2 x = - 6 \color{#FF6800}{ + } \color{#FF6800}{ 4 }$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = - 6 + 4$
 Organize the expression 
$\color{#FF6800}{ x } = - 6 + 4$
$x = \color{#FF6800}{ - } \color{#FF6800}{ 6 } \color{#FF6800}{ + } \color{#FF6800}{ 4 }$
 Add $- 6$ and $4$
$x = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
 그래프 보기 
Graph
Solution search results